An Inquiry by Social Workers into Evening Routines in Community Living Settings for Adults with Learning Disabilities. Issue 1 (1st January 2018) - James, Elaine; Harvey, Mark; Mitchell, Rob
Abstract : Significant progress has been made since the 1980s in supporting adults with learning disability to live independent lives in the community. In 2012, the Department of Health in England announced the latest policy initiative to further invest in community support for people with learning disabilities, Transforming Care. Building the right community supported living setting for people does not in isolation provide for a comprehensive strategy towards achieving a paradigm shift in how people with learning disabilities experience their full right to inclusion in their communities. We undertook a practice inquiry into the quality of life experienced by people with learning disabilities. Social workers chose the focus of the inquiry to be on people's evening routines to answer the question — were people living in the community experiencing independence or did institutional routines define their lives. The findings were that 69% of people with a learning disability were either in bed or were ready for bed. There was evidence that institutionalised routines existed in the settings with an association between an early evening meal time and the person being ready for or in bed ( p  = 0.0001 at Time 1 and p  = 0.051 at Time 2). Implications for social work practice are discussed.